Exploring internet techonologies for competitive advantages - Giam, Kim Toh. (2008)
To survive in this information age, a company can no longer compete based on cost and quality alone. It needs also to be able to manage its information effectively in order to speed up time-to-market, open new markets, attract and retain customers, and create new opportunities for growth.